Low Self‐Reported Function Predicts Adverse Postoperative Course in Veterans Affairs Beneficiaries Undergoing Total Hip and Total Knee Replacement. Issue 4 (April 2016) - Kapoor, Alok; Chew, Priscilla W.; Reisman, Joel I.; Berlowitz, Dan R.
Abstract : Objectives: To measure association between self‐reported function and an adverse postoperative course and improvement in performance on the American College of Surgeons Universal Risk Calculator (ACS calculator) with inclusion of self‐reported function available through the Veteran Rand‐12 based Physical Component Summary (PCS) and Mental Component Summary (MCS) scores. Design: Cohort analysis. Setting: Veteran Affairs health system. Participants: Surgeries (n = 3, 503) for older male veterans undergoing hip and knee replacement from 2002 to 2009. Measurements: Serious complication (per ACS definition), discharge to facility, readmission, and death within 30 days after surgery as a function of PCS and MCS; comparison of prediction of net reclassification index (NRI) for serious complication using a modified version of the ACS calculator with prediction using the ACS calculator with MCS and PCS added. Results: Being in the lowest PCS quartile (vs highest quartile) predicted more than twice the risk of a serious complication (odds ratio (OR) = 2.27, 95% confidence interval (CI) = 1.44–3.58), twice the risk of discharge to facility (OR = 1.97, 95% CI = 1.39–2.79), and almost twice the risk of readmission (OR = 1.80, 95% CI = 1.37–2.36). The lowest quartile of MCS predicted each outcome, although to a lesser extent than PCS. The enhanced model had a NRI of 29.4% (95% CI = 15.4–43.3%), reflecting that 20.8% of events were appropriately upgraded and 8.6% of nonevents appropriately downgraded. Conclusion: Low PCS and MCS predicted an adverse postoperative course and enhanced the ACS calculator. Clinicians evaluating older adults undergoing orthopedic surgery could enhance the accuracy of their assessments by including self‐reported functional status.